Evaluating RBC indices in the differential diagnosis between iron deficiency anemia and beta-thalassemia trait - الشمالي, سوزان; حسين, فراس; عمران, ريم (Latakia University Journal -Medical Sciences Series, 2021)
Background: Anemia affects more than third of world's population and microcytic hypochromic anemia constitute an important part of anemia Iron deficiency anemia IDA and beta thalassemia trait BTT are the most common causes of microcytic hypochromic anemia particulary in Syria To confirm diagnosis we depend on iron studies (iron-TIBC-transferrin receptors) for IDA and hemoglobin analysis for BTT Purpose: to evaluate the role of RBC indices and formulas in the differential diagnosis between iron deficiency anemia (IDA) and beta-thalassemia trait (BTT) by comparing them with the gold standards of diagnosis. Methods: This study included 110 outpatients and with hypochromic microcytic anemia according to their complete blood count, all of them underwent the following blood tests: CRP-Ferritin- Hb A2 measurement by hemoglobin electrophoresis\HPLC, and then distributed into 2 groups: 50 patients with iron deficiency anemia, 50 patients with beta thalassemia trait. Ten patients were found to have both IDA and BTT. The study took place in the central laboratory at Tishreen University Hospital in Latakia, between June 2020 and February 2021. Results: Jayabose was the best discriminant index according to Youden index that is based on sensitivity and specificity (sensitivity+specificity-100) England and Fraser and Srivastava was the best index for diagnosis of IDA and Ricerca was the best index for diagnosis of BTT The best cut-off of jayabose was found to be at the point 224 by using Receiver Operation Characteristic (ROC Curve) Conclusion: according to Youden index, the most important index to discriminate between iron deficiency anemia and beta thalassemia trait was jayabose, and its cut-off is at the point 224